Hydrogel-cement-based composite grouting material capable of being used underwater

By preparing hydrogel-cement-based composite grouting material, the water absorption characteristics of the strengthened hydrogel are used to improve the dispersion resistance under dynamic water, and the problem of construction difficulties of grouting material in the prior art in the water environment is solved, and the rapid repair of concrete structures is achieved.

CN119774941AActive Publication Date: 2025-04-08SOUTHEAST UNIV

Patent Information

Application Number
CN202411834943.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing underwater resistant dispersion grouting material is difficult to effectively construct in a water-moving environment, and the anti-dispersant has an adverse effect on the hardening of the grouting material.

Method used

A hydrogel-cement-based composite grouting material was used to mix polyvinyl alcohol and sodium alginate, and add ettringite fibers and calcium chloride for cross-linking reaction, a reinforced hydrogel was prepared, and a grouting material was made by combining cement and water.

Benefits of technology

It significantly improves the anti-dispersion performance of the grouting material under dynamic water, reduces the dispersion of the grouting material, and realizes rapid repair of the concrete structure under dynamic water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774941A_ABST
    Figure CN119774941A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of grouting materials, and particularly relates to a hydrogel-cement-based composite grouting material capable of being used underwater, which is prepared from the following raw materials in parts by weight: 99.5 to 99.98 parts of cement, 0.02 to 0.5 part of reinforced hydrogel and 80 to 100 parts of water, the reinforced hydrogel is prepared by adopting a method comprising the following steps: (1) uniformly mixing a polyvinyl alcohol solution and a sodium alginate solution, and stirring in an ice-water bath; (2) adding a cement hydration product phase-ettringite fiber dispersion liquid, and uniformly stirring; (3) adding a calcium chloride solution, and carrying out cross-linking reaction; (4) crushing and drying the cross-linked product to obtain solid particles; and (5) soaking the solid particles in a mixed solution of glutaraldehyde and hydrochloric acid to obtain the reinforced hydrogel. According to the composite grouting material, the underwater dispersion resistance of the grouting material can be greatly improved, and the composite grouting material is especially suitable for underwater grouting repair engineering at a high flow rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of grouting materials, and in particular relates to a hydrogel-cement-based composite grouting material that can be used under dynamic water. Background Art

[0002] As engineering structures are increasingly moving towards complex service environments such as underwater and offshore. However, in a water-rich environment, complex ions and other harmful substances carried by water as a transmission medium invade the interior of concrete materials, accelerating the degradation of concrete structure performance. This urgently requires the development of matching underwater repair materials and repair methods. Underwater repair puts higher requirements on traditional repair materials. Against this background, underwater anti-dispersion grouting materials have emerged, which are widely used in water conservancy projects, offshore oil platforms, cross-river and cross-sea bridges and other projects. Underwater anti-dispersion grouting materials can be used for caisson bottom sealing, cofferdams, caissons, riprap grouting, underwater continuous wall pouring, underwater foundation leveling and filling, as well as large-diameter cast-in-place piles, docks, dams, reservoir repairs and other projects. In addition, it can also be used for underwater abutments, seawall revetments, slope protection, pile sealing and plugging, and underwater projects where ordinary concrete is difficult to construct.

[0003] Existing underwater anti-dispersion grouting materials mainly improve the anti-dispersion, hardening rate and early strength of the grouting materials by adding admixtures. For example: the use of polycarboxylic acid water reducer can regulate the fluidity of the slurry; sodium gluconate is used as a retarder to adjust the setting time; the early strength agent adjusts the strength of the slurry stone body; hydroxyethyl methyl cellulose ether is used as an anti-dispersion agent to improve the anti-dispersion performance of the slurry; silica fume is used as a mineral additive to improve the physical and mechanical properties of the slurry. However, this type of underwater anti-dispersion grouting material is mostly used in underwater construction with a low water flow rate, and the anti-dispersion agent of hydroxyethyl methyl cellulose ether will have an adverse effect on the hardening of the grouting material, affecting its construction application in a dynamic water environment.

[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a hydrogel-cement-based composite grouting material that can be used under moving water, so as to facilitate the construction of the grouting material under moving water and reduce the dispersion of the grouting material under moving water.

[0006] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a hydrogel-cement-based composite grouting material that can be used under dynamic water, the underwater anti-dispersion grouting material comprising the following raw materials in parts by weight: 99.5-99.98 parts of cement, 0.02-0.5 parts of reinforced hydrogel and 80-100 parts of water; the reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing a polyvinyl alcohol solution and a sodium alginate solution evenly, and stirring in an ice water bath; (2) adding a calcium aluminate fiber dispersion to the mixture obtained by the treatment of step (1), and stirring evenly; (3) adding a calcium chloride solution to the mixed solution obtained by the treatment of step (2), and cross-linking reaction; (4) crushing and drying the cross-linked product obtained after the cross-linking reaction to obtain solid particles; (5) soaking the solid particles in a mixed solution of glutaraldehyde and hydrochloric acid, and after the soaking, the reinforced hydrogel is obtained.

[0007] Preferably, in step (1), the concentration of the polyvinyl alcohol solution and / or the sodium alginate solution is 2wt%, and the mass ratio of the polyvinyl alcohol solution to the sodium alginate solution is (8-10):9; the polyvinyl alcohol solution is prepared by dissolving polyvinyl alcohol in deionized water at 60-90°C.

[0008] Preferably, the ettringite fiber is prepared by a method comprising the following steps: uniformly mixing sulphoaluminate cement clinker and water, hydrating at 60-70°C for 70-74h, separating the solid and liquid, and drying to obtain the ettringite fiber; the mass ratio of the sulphoaluminate cement clinker to water is 1:(8-10).

[0009] Preferably, in step (2), the mass ratio of the ettringite fiber in the ettringite fiber dispersion to the polyvinyl alcohol solution is (2-2.5):9; in step (2), after adding the ettringite fiber dispersion, the stirring time is 0.5-1.5h.

[0010] Preferably, in step (3), the concentration of the calcium chloride solution is 1.5wt%, and the mass ratio of the calcium chloride solution to the polyvinyl alcohol solution is 2-2.5; in step (3), the time of the cross-linking reaction is 2.5-3.5h.

[0011] Preferably, in step (5), the mass ratio of the glutaraldehyde solution to the hydrochloric acid solution is (45-50):3; and the concentration of the glutaraldehyde solution is 50wt%.

[0012] Preferably, the cement is at least one of silicate cement, phosphate cement and sulphoaluminate cement.

[0013] Beneficial effects:

[0014] The components of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention include reinforced hydrogel, which helps to greatly improve the underwater anti-dispersion ability of the grouting material, especially for underwater grouting repair projects under high flow rates.

[0015] Traditional anti-dispersion grouting materials are often formed by compounding admixtures such as accelerators and thickeners with cement-based materials. After the slurry is injected, it is difficult to agglomerate and form (traditional anti-dispersion grouting materials mainly improve the anti-dispersion performance by increasing the viscosity of the grouting materials); while the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention can rely on the water absorption characteristics of the reinforced hydrogel to absorb and agglomerate the relatively dispersed grouting materials together, thereby enhancing the integrity of the grouting material (the reinforced hydrogel in the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention has little effect on the viscosity of the grouting material). In addition, traditional underwater grouting materials are highly dependent on the content of admixtures. A slight change in the content of admixtures will cause a significant change in the performance of the grouting material, resulting in large fluctuations in the performance of traditional grouting materials and a small control range; the present invention mainly relies on the water-controlling characteristics of the reinforced hydrogel, and realizes wide-threshold control and precise design of the performance of the grouting material by regulating the water absorption multiple of the reinforced hydrogel, the water absorption rate, the setting time of the cement, and the ratio of the reinforced hydrogel to the cement, thereby helping to achieve rapid repair of concrete structures under different water flow rates. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0017] Figure 1 It is a state diagram of the hydrogel-cement-based composite grouting material of the present invention that can be used under dynamic water. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0019] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0020] The invention provides a hydrogel-cement-based composite grouting material that can be used under moving water, so as to facilitate the construction of the grouting material under moving water and reduce the dispersion of the grouting material under moving water.

[0021] The hydrogel-cement-based composite grouting material that can be used under dynamic water according to the embodiment of the present invention comprises the following raw materials in parts by weight: 99.5-99.98 parts of cement (for example, 99.5 parts, 99.6 parts, 99.7 parts, 99.8 parts or 99.98 parts), 0.02-0.5 parts of reinforced hydrogel (for example, 0.02 parts, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts) and 80-100 parts of water (for example, 80 parts, 85 parts, 90 parts, 95 parts or 100 parts); reinforced hydrogel The method is prepared by the following steps: (1) mixing a polyvinyl alcohol solution and a sodium alginate solution uniformly and stirring in an ice water bath; (2) adding a calcium aluminate fiber dispersion to the mixture obtained by the treatment of step (1) and stirring uniformly; (3) adding a calcium chloride solution to the mixed solution obtained by the treatment of step (2) to carry out a cross-linking reaction; (4) crushing and drying the cross-linked product obtained after the cross-linking reaction to obtain solid particles; (5) soaking the solid particles in a mixed solution of glutaraldehyde and hydrochloric acid, and after the soaking is completed, a reinforced hydrogel is obtained.

[0022] The hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention can rely on the water absorption characteristics of the reinforced hydrogel (the reinforced hydrogel is prepared by a specific method using sodium alginate and polyvinyl alcohol as main raw materials; if sodium alginate or polyvinyl alcohol is used alone, the gelation will be affected) to adsorb and agglomerate relatively dispersed grouting materials together, thereby enhancing the integrity of the grouting materials, thereby significantly improving the anti-dispersion performance of the grouting materials under dynamic water, and helping to achieve rapid repair of concrete structures under dynamic water.

[0023] Preferably, the amount of the reinforced hydrogel is 0.2-0.5 parts.

[0024] In a preferred embodiment of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention, in step (1), the concentration of the polyvinyl alcohol solution and / or the sodium alginate solution is 2wt%, and the mass ratio of the polyvinyl alcohol solution to the sodium alginate solution is (8-10):9 (for example, 8:9, 8.5:9, 9:9, 9.5:9, or 10:9); the polyvinyl alcohol solution is prepared by dissolving polyvinyl alcohol in deionized water at 60-90°C (for example, 60°C, 70°C, 80°C or 90°C).

[0025] In a preferred embodiment of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention, the ettringite fiber is prepared by a method comprising the following steps: sulphoaluminate cement clinker and water are uniformly mixed, hydrated at 60-70°C (for example, 60°C, 62°C, 64°C, 66°C, 68°C or 70°C) for 70-74h (for example, 70h, 71h, 72h, 73h or 74h), solid-liquid separation, and drying to obtain the ettringite fiber; the mass ratio of sulphoaluminate cement clinker to water is 1:(8-10) (for example, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10).

[0026] In a preferred embodiment of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention, in step (2), the mass ratio of the ettringite fiber to the polyvinyl alcohol solution in the ettringite fiber dispersion is (2-2.5):9 (for example, 2:9, 2.1:9, 2.2:9, 2.3:9, 2.4:9 or 2.5:9); in step (2), after adding the ettringite fiber dispersion, the stirring time is 0.5-1.5h (for example, 0.5h, 0.8h, 1.0h, 1.2h or 1.5h; it is sufficient to achieve uniform mixing of the ettringite fiber dispersion and other raw materials).

[0027] In a preferred embodiment of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention, in step (3), the concentration of the calcium chloride solution is 1.5wt%, and the mass ratio of the calcium chloride solution to the polyvinyl alcohol solution is 2-2.5 (for example, 2, 2.1, 2.2, 2.3, 2.4 or 2.5); in step (3), the cross-linking reaction time is 2.5-3.5h (for example, 2.5h, 2.8h, 3h, 3.2h or 3.5h).

[0028] In a preferred embodiment of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention, in step (5), the mass ratio of glutaraldehyde solution to hydrochloric acid solution is (45-50):3 (for example, 45:3, 46:3, 47:3, 48:3, 49:3 or 50:3); the concentration of glutaraldehyde solution is 50wt%, and the concentration of hydrochloric acid solution is 1mol / L.

[0029] In a preferred embodiment of the hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention, the cement is at least one of silicate cement, phosphate cement and sulphoaluminate cement.

[0030] The hydrogel-cement-based composite grouting material that can be used under dynamic water of the present invention is described in detail below through specific examples.

[0031] In the following embodiments:

[0032] The cement is 72.5 grade sulphoaluminate cement; the polyvinyl alcohol solution is obtained by dissolving polyvinyl alcohol in deionized water at a mass fraction of 2% (Mw of polyvinyl alcohol is 89000-98000, 99% hydrolyzed); the sodium alginate solution is obtained by dissolving sodium alginate (analytical grade, Aladdin) in deionized water at a mass fraction of 2%; the CaCl2 solution is a 1.5wt% CaCl2 aqueous solution; the ettringite fiber is obtained by hydrating sulphoaluminate cement clinker in deionized water at 70°C for 72 hours ( The water-to-solid ratio is 10) to obtain an ettringite fiber solution, and ultrasonic dispersion is performed for 5 minutes to obtain an ettringite fiber dispersion; the glutaraldehyde solution is a 50wt% deionized water solution of glutaraldehyde (analytical grade, Aladdin); the hydrochloric acid solution (1mol / L) is a diluted solution of concentrated hydrochloric acid; the water is deionized water; the ice water bath is provided by a magnetic stirring cold water bath pot to provide a water bath environment of 5°C, and the warm water bath is provided by a magnetic stirring hot water bath pot, and the temperature is between 60°C and 90°C; the grouting material is stirred by a rotary mixer.

[0033] Example 1

[0034] The hydrogel-cement-based composite grouting material that can be used under dynamic water in this embodiment includes the following components in parts by weight: 99.98 parts of cement, 0.02 parts of reinforced hydrogel and 80 parts of water.

[0035] Among them, the raw materials for strengthening the hydrogel include, by weight: 45 parts of polyvinyl alcohol solution, 45 parts of sodium alginate solution, 10 parts of ettringite fiber, 100 parts of CaCl2 solution, 94.34 parts of glutaraldehyde solution and 5.66 parts of dilute hydrochloric acid solution.

[0036] The reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing polyvinyl alcohol solution and sodium alginate in a warm water bath, then storing them in an ice water bath, and uniformly stirring them in a magnetic stirring water bath to polymerize them, with the rotor rotating at a speed of 500 r / min; (2) adding calcium aluminate fiber dispersion to the above mixed solution, and then stirring for 1 hour; (3) pouring the above solution into a CaCl2 solution and cross-linking for 3 hours; (4) placing the cross-linked product obtained in the above steps into a small crusher and crushing it for 1.5 minutes to obtain small particles (particle size less than 0.5 cm), and further drying to obtain dry solid particles; (5) in order to further increase the degree of cross-linking, immersing it in a mixed solution of glutaraldehyde solution and hydrochloric acid solution (the mass ratio of glutaraldehyde solution to hydrochloric acid solution is 50:3) at room temperature for 1 hour to obtain a reinforced hydrogel.

[0037] Cement, water and reinforced hydrogel (before mixing with cement, the reinforced hydrogel prepared in step (5) is cleaned and soaked to remove residual reaction raw materials) are mixed in a mortar mixer according to proportion. The rotation speed of the mortar mixer is 300 r / min and the mixing time is 120 s. Stop the mixing instrument to obtain a hydrogel-cement composite underwater anti-dispersion grouting material.

[0038] Example 2

[0039] The hydrogel-cement-based composite grouting material that can be used under dynamic water in this embodiment includes the following components in parts by weight: 99.95 parts of cement, 0.05 parts of reinforced hydrogel and 80 parts of water.

[0040] Among them, the raw materials for strengthening the hydrogel include, by weight: 45 parts of polyvinyl alcohol solution, 45 parts of sodium alginate solution, 10 parts of ettringite fiber, 100 parts of CaCl2 solution, 94.34 parts of glutaraldehyde solution and 5.66 parts of dilute hydrochloric acid solution.

[0041] The reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing polyvinyl alcohol solution and sodium alginate in a warm water bath, then storing in an ice water bath, and uniformly stirring in a magnetic stirring water bath to polymerize the mixture, with the rotor rotating at a speed of 500 r / min; (2) ultrasonically dispersing calcium sulfoxide fiber in deionized water for 5 minutes, adding the mixed solution, and then stirring for 1 hour; (3) pouring the solution into a CaCl2 solution and cross-linking for 3 hours; (4) placing the cross-linked product obtained in the above steps into a small crusher and crushing it for 1.5 minutes to obtain small particles (particle size less than 0.5 cm), and further drying to obtain dry solid particles; (5) in order to further increase the degree of cross-linking, immersing it in a mixed solution of glutaraldehyde solution and hydrochloric acid solution (the mass ratio of glutaraldehyde solution to hydrochloric acid solution is 50:3) at room temperature for 1 hour to obtain a reinforced hydrogel.

[0042] Cement, water and reinforced hydrogel (before mixing with cement, the reinforced hydrogel prepared in step (5) is cleaned and soaked to remove residual reaction raw materials) are mixed in a mortar mixer according to proportion. The rotation speed of the mortar mixer is 300 r / min and the mixing time is 120 s. Stop the mixing instrument to obtain a hydrogel-cement composite underwater anti-dispersion grouting material.

[0043] Example 3

[0044] The hydrogel-cement-based composite grouting material that can be used under dynamic water in this embodiment includes the following components in parts by weight: 99.90 parts of cement, 0.10 parts of reinforced hydrogel and 80 parts of water.

[0045] Among them, the raw materials for strengthening the hydrogel include, by weight: 45 parts of polyvinyl alcohol solution, 45 parts of sodium alginate solution, 10 parts of ettringite fiber, 100 parts of CaCl2 solution, 94.34 parts of glutaraldehyde solution and 5.66 parts of dilute hydrochloric acid solution.

[0046] The reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing polyvinyl alcohol solution and sodium alginate in a warm water bath, then storing in an ice water bath, and uniformly stirring in a magnetic stirring water bath to polymerize the mixture, with the rotor rotating at a speed of 500 r / min; (2) ultrasonically dispersing calcium sulfoxide fiber in deionized water for 5 minutes, adding the mixed solution, and then stirring for 1 hour; (3) pouring the solution into a CaCl2 solution and cross-linking for 3 hours; (4) placing the cross-linked product obtained in the above steps into a small crusher and crushing it for 1.5 minutes to obtain small particles (particle size less than 0.5 cm), and further drying to obtain dry solid particles; (5) in order to further increase the degree of cross-linking, immersing it in a mixed solution of glutaraldehyde solution and hydrochloric acid solution (the mass ratio of glutaraldehyde solution to hydrochloric acid solution is 50:3) at room temperature for 1 hour to obtain a reinforced hydrogel.

[0047] Cement, water and reinforced hydrogel (before mixing with cement, the reinforced hydrogel prepared in step (5) is cleaned and soaked to remove residual reaction raw materials) are mixed in a mortar mixer according to proportion. The rotation speed of the mortar mixer is 300 r / min and the mixing time is 120 s. Stop the mixing instrument to obtain a hydrogel-cement composite underwater anti-dispersion grouting material.

[0048] Example 4

[0049] The hydrogel-cement-based composite grouting material that can be used under dynamic water in this embodiment includes the following components in parts by weight: 99.80 parts of cement, 0.20 parts of reinforced hydrogel and 80 parts of water.

[0050] Among them, the raw materials for strengthening the hydrogel include, by weight: 45 parts of polyvinyl alcohol solution, 45 parts of sodium alginate solution, 10 parts of ettringite fiber, 100 parts of CaCl2 solution, 94.34 parts of glutaraldehyde solution and 5.66 parts of dilute hydrochloric acid solution.

[0051] The reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing polyvinyl alcohol solution and sodium alginate in a warm water bath, then storing in an ice water bath, and uniformly stirring in a magnetic stirring water bath to polymerize the mixture, with the rotor rotating at a speed of 500 r / min; (2) ultrasonically dispersing calcium sulfoxide fiber in deionized water for 5 minutes, adding the mixed solution, and then stirring for 1 hour; (3) pouring the solution into a CaCl2 solution and cross-linking for 3 hours; (4) placing the cross-linked product obtained in the above steps into a small crusher and crushing it for 1.5 minutes to obtain small particles (particle size less than 0.5 cm), and further drying to obtain dry solid particles; (5) in order to further increase the degree of cross-linking, immersing it in a mixed solution of glutaraldehyde solution and hydrochloric acid solution (the mass ratio of glutaraldehyde solution to hydrochloric acid solution is 50:3) at room temperature for 1 hour to obtain a reinforced hydrogel.

[0052] Cement, water and reinforced hydrogel (before mixing with cement, the reinforced hydrogel prepared in step (5) is cleaned and soaked to remove residual reaction raw materials) are mixed in a mortar mixer according to proportion. The rotation speed of the mortar mixer is 300 r / min and the mixing time is 120 s. Stop the mixing instrument to obtain a hydrogel-cement composite underwater anti-dispersion grouting material.

[0053] Example 5

[0054] The hydrogel-cement-based composite grouting material that can be used under dynamic water in this embodiment includes the following components in parts by weight: 99.50 parts of cement, 0.50 parts of reinforced hydrogel and 80 parts of water.

[0055] Among them, the raw materials for strengthening the hydrogel include, by weight: 45 parts of polyvinyl alcohol solution, 45 parts of sodium alginate solution, 10 parts of ettringite fiber, 100 parts of CaCl2 solution, 94.34 parts of glutaraldehyde solution and 5.66 parts of dilute hydrochloric acid solution.

[0056] The reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing polyvinyl alcohol solution and sodium alginate in a warm water bath, then storing in an ice water bath, and uniformly stirring in a magnetic stirring water bath to polymerize the mixture, with the rotor rotating at a speed of 500 r / min; (2) ultrasonically dispersing calcium sulfoxide fiber in deionized water for 5 minutes, adding the mixed solution, and then stirring for 1 hour; (3) pouring the solution into a CaCl2 solution and cross-linking for 3 hours; (4) placing the cross-linked product obtained in the above steps into a small crusher and crushing it for 1.5 minutes to obtain small particles (particle size less than 0.5 cm), and further drying to obtain dry solid particles; (5) in order to further increase the degree of cross-linking, immersing it in a mixed solution of glutaraldehyde solution and hydrochloric acid solution (the mass ratio of glutaraldehyde solution to hydrochloric acid solution is 50:3) at room temperature for 1 hour to obtain a reinforced hydrogel.

[0057] Cement, water and reinforced hydrogel (before mixing with cement, the reinforced hydrogel prepared in step (5) is cleaned and soaked to remove residual reaction raw materials) are mixed in a mortar mixer according to proportion. The rotation speed of the mortar mixer is 300 r / min and the mixing time is 120 s. Stop the mixing instrument to obtain a hydrogel-cement composite underwater anti-dispersion grouting material.

[0058] Example 6

[0059] The hydrogel-cement-based composite grouting material that can be used under dynamic water in this embodiment includes the following components in parts by weight: 99.50 parts of cement, 0.50 parts of reinforced hydrogel and 100 parts of water.

[0060] Among them, the raw materials for strengthening the hydrogel include, by weight: 45 parts of polyvinyl alcohol solution, 45 parts of sodium alginate solution, 10 parts of ettringite fiber, 100 parts of CaCl2 solution, 94.34 parts of glutaraldehyde solution and 5.66 parts of dilute hydrochloric acid solution.

[0061] The reinforced hydrogel is prepared by a method comprising the following steps: (1) mixing polyvinyl alcohol solution and sodium alginate in a warm water bath, then storing in an ice water bath, and uniformly stirring in a magnetic stirring water bath to polymerize the mixture, with the rotor rotating at a speed of 500 r / min; (2) ultrasonically dispersing calcium sulfoxide fiber in deionized water for 5 minutes, adding the mixed solution, and then stirring for 1 hour; (3) pouring the solution into a CaCl2 solution and cross-linking for 3 hours; (4) placing the cross-linked product obtained in the above steps into a small crusher and crushing it for 1.5 minutes to obtain small particles (particle size less than 0.5 cm), and further drying to obtain dry solid particles; (5) in order to further increase the degree of cross-linking, immersing it in a mixed solution of glutaraldehyde solution and hydrochloric acid solution (the mass ratio of glutaraldehyde solution to hydrochloric acid solution is 50:3) at room temperature for 1 hour to obtain a reinforced hydrogel.

[0062] Cement, water and reinforced hydrogel (before mixing with cement, the reinforced hydrogel prepared in step (5) is cleaned and soaked to remove residual reaction raw materials) are mixed in a mortar mixer according to proportion. The rotation speed of the mortar mixer is 300 r / min and the mixing time is 120 s. Stop the mixing instrument to obtain a hydrogel-cement composite underwater anti-dispersion grouting material.

[0063] Comparative Example 1

[0064] The grouting material of this comparative example includes the following components in parts by weight: 99.98 parts of cement and 80 parts of water; the cement and water are placed in a mortar mixer with a rotation speed of 300 r / min and a mixing time of 120 s; the mixing device is stopped to obtain the grouting material of this comparative example.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 5 is that step (2) is omitted (that is, the step of adding ettringite fibers is omitted); the rest is consistent with Example 5.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 5 is that the amount of calcium aluminate fiber used in step (2) is 20 parts; the rest is consistent with Example 5.

[0069] Comparative Example 4

[0070] The difference between this comparative example and Example 5 is that the amount of calcium aluminate fiber used in step (2) is 5 parts; the rest is consistent with Example 5.

[0071] Comparative Example 5

[0072] The difference between this comparative example and Example 5 is that step (5) is omitted (that is, the step of soaking the dried solid particles obtained in step (4) with a mixed solution of glutaraldehyde and hydrochloric acid is omitted); the rest is consistent with Example 5.

[0073] Comparative Example 6

[0074] The difference between this comparative example and Example 5 is that in step (3), the CaCl2 solution is poured in, and step (4) is performed after cross-linking for 1 hour; the rest is consistent with Example 5.

[0075] Comparative Example 7

[0076] The difference between this comparative example and Example 5 is that in step (3), the mixture is poured into a CaCl2 solution and step (4) is performed after cross-linking for 5 hours; the rest is consistent with Example 5.

[0077] Performance testing:

[0078] The scouring loss rate of the grouting materials of the above-mentioned Examples 1-6 and Comparative Examples 1-7 was tested.

[0079] Test method: In order to determine the underwater scouring loss rate of the grouting material, each sample was tested 3 times; a petri dish was set at the bottom of a beaker containing 1000 mL of water, and a uniform speed stirring head with a rotation speed of 250 r / min was set on the water surface to simulate the water flow environment; during the uniform speed stirring of the rotor, M0 (50 g) of grouting material was taken each time and injected into the petri dish at the bottom of the beaker (grouting can be performed with the help of a grouting tube), and after 2 minutes, the petri dish was taken out and the mass M of the remaining grouting material was weighed n The underwater scouring loss rate of the grouting material is calculated by formula (1).

[0080] S=(M0-Mn ) / M0 (1)

[0081] Wherein, S is the underwater scouring loss rate of the grouting material; M0 is the mass of the initial grouting material, which is 50g in this embodiment; M n It is the remaining mass of the grouting material after 2 minutes (the sulphoaluminate cement used in the composite grouting materials of Examples 1-6 is fast-hardening cement, so that the composite grouting materials of Examples 1-6 can harden quickly; the slurry lost within the first 2 minutes of grouting can reach more than 85% of the total loss of the grouting material under dynamic water; after 2 minutes of grouting, a large amount of grouting material will basically not be washed away by dynamic water; therefore, when conducting the scouring loss rate test, the present invention characterizes the early anti-dispersion performance of the grouting material by testing the scouring loss rate after grouting for 2 minutes under dynamic water).

[0082] The results are shown in Table 1 below.

[0083] Table 1 Scour loss rate test results

[0084]

[0085]

[0086] From the results in Table 1 above, it can be seen that in Examples 1-5, as the content of the reinforced hydrogel increases, the mass loss rate of the grouting material under dynamic water gradually decreases; when the mass ratio of the reinforced hydrogel / cement reaches 0.5%, the underwater loss rate of the grouting material is only 16.8%. Compared with Comparative Example 1, the scouring loss rate of the grouting material of Example 5 under dynamic water environment is reduced by 77.6%.

[0087] Compared with Comparative Example 2, the grouting material of Example 5 also has a significantly lower scour loss rate in a dynamic water environment. The main mechanism is that the calcium aluminate fiber increases the cross-linking degree of the hydrogel, thereby improving its mechanical properties and expansibility; on the other hand, the calcium aluminate fiber extends the underwater life of the hydrogel and improves the anti-dispersion and aging resistance of the hydrogel.

[0088] The experimental results of Comparative Examples 3 and 4 and Example 5 show that only an appropriate amount of ettringite fiber can effectively improve the performance of the hydrogel material, while too little or too much is unlikely to achieve a similar effect.

[0089] Comparison of the experimental results of Comparative Examples 5, 6, and 7 with those of Example 5 shows that insufficient or excessive crosslinking time will lead to poor performance of the hydrogel and affect the anti-dispersion performance of the cement-based grouting material; on the one hand, too short a crosslinking time will reduce the water absorption rate of the hydrogel and reduce the agglomeration of the grouting material in a dynamic water environment; on the other hand, too long a crosslinking time will cause the hydrogel to have poor toughness and be easily broken. In addition, by Figure 1It can be seen that under the action of dynamic water, a sufficient content of reinforced hydrogel can significantly improve the anti-dispersion ability of the grouting material.

[0090] In summary: The use of reinforced hydrogel can significantly improve the anti-dispersion performance of fast-hardening cement-based grouting materials. The main reason is that the reinforced hydrogel has a higher specific surface area, and the fiber-reinforced structure can absorb liquid cement slurry with water as the main component, thereby hindering the dispersion of cement slurry under moving water and improving the agglomeration of the grouting material. In addition, compared with traditional anti-dispersion grouting materials, the hydrogel-cement-based composite grouting material that can be used under moving water of the present invention also has the following advantages: (1) Traditional anti-dispersion grouting materials often improve the anti-dispersion performance of the grouting material by changing the cement components, such as using silica fume, reducing the water-cement ratio, etc., while the present invention can achieve such effects without changing the cement components (the cement components have little effect on the composite grouting material of the present invention); and changing the cement components is also applicable to the present invention. In such cases, the grouting material properties can be further improved; (2) Traditional anti-dispersion grouting materials use thickeners and early agents to improve the anti-dispersion performance of the grouting material. Such inventions sacrifice some of the properties of the grouting material (such as using Thickeners and early strength agents often significantly reduce the early fluidity or pumpability of grouting materials, greatly shorten the grouting window period of grouting materials, and are inconvenient for construction. Or the use of early strength agents often causes the strength of grouting materials to shrink in the later stage. The strength of the composite grouting material of the present invention increases with age, and there will be no strength shrinkage. (3) The performance control range of traditional anti-dispersion grouting materials is small and the designability is poor. Generally speaking, the content of admixtures in traditional methods is relatively low, and slight changes in admixtures will cause drastic changes in the performance of the grouting materials, and the controllability is not strong. However, the grouting material of the present invention can adjust the dosage ratio of the reinforcing hydrogel according to actual needs (for example, the requirements for anti-dispersion performance), and has strong designability.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A hydrogel-cement-based composite grouting material that can be used under dynamic water, characterized in that: The underwater anti-dispersion grouting material comprises the following raw materials in parts by weight: 99.5-99.98 parts of cement, 0.02-0.5 parts of reinforced hydrogel and 80-100 parts of water; The reinforced hydrogel is prepared by a method comprising the following steps: (1) Mix the polyvinyl alcohol solution and the sodium alginate solution evenly and stir in an ice water bath; (2) adding the ettringite fiber dispersion to the mixture obtained in step (1) and stirring evenly; (3) adding calcium chloride solution to the mixed solution obtained by step (2) to carry out a cross-linking reaction; (4) crushing and drying the cross-linked product obtained after the cross-linking reaction to obtain solid particles; (5) Soaking the solid particles in a mixed solution of glutaraldehyde and hydrochloric acid, and after the soaking is completed, the reinforced hydrogel is obtained.

2. The hydrogel-cement-based composite grouting material that can be used under dynamic water according to claim 1, characterized in that: In step (1), the concentration of the polyvinyl alcohol solution and / or the sodium alginate solution is 2 wt %, and the mass ratio of the polyvinyl alcohol solution to the sodium alginate solution is (8-10):9; The polyvinyl alcohol solution is prepared by dissolving polyvinyl alcohol in deionized water at 60-90°C.

3. The hydrogel-cement-based composite grouting material that can be used under dynamic water according to claim 1, characterized in that: The ettringite fiber is prepared by a method comprising the following steps: uniformly mixing sulphoaluminate cement clinker with water, hydrating at 60-70° C. for 70-74 hours, separating the solid from the liquid, and drying to obtain the ettringite fiber; The mass ratio of the sulphoaluminate cement clinker to water is 1:(8-10).

4. The hydrogel-cement-based composite grouting material that can be used under dynamic water according to claim 1, characterized in that: In step (2), the mass ratio of the ettringite fiber in the ettringite fiber dispersion to the polyvinyl alcohol solution is (2-2.5):9; In step (2), after adding the ettringite fiber dispersion, the stirring time is 0.5-1.5h.

5. The hydrogel-cement-based composite grouting material that can be used under dynamic water according to claim 1, characterized in that: In step (3), the concentration of the calcium chloride solution is 1.5wt%, and the mass ratio of the calcium chloride solution to the polyvinyl alcohol solution is 2-2.5; In step (3), the cross-linking reaction time is 2.5-3.5 hours.

6. The hydrogel-cement-based composite grouting material that can be used under dynamic water according to claim 1, characterized in that: In step (5), the mass ratio of the glutaraldehyde solution to the hydrochloric acid solution is (45-50):3; The concentration of the glutaraldehyde solution is 50 wt %.

7. The hydrogel-cement-based composite grouting material that can be used under dynamic water according to claim 1, characterized in that: The cement is at least one of silicate cement, phosphate cement and sulphoaluminate cement.

Citation Information

Patent Citations

  • Reinforcing slurry for underwater concrete and preparation process of reinforcing slurry

    CN114685112A

  • Cement-based underwater repair material and preparation method thereof

    CN118684459A

  • Double-liquid grouting slurry, its technology and application for super large diameter underwater shield engineering under high water pressure condition

    US20230212076A1

  • Compositions and methods for manufacturing ettringite coated fibers and aggregates

    US5786080A

Cited By

  • Diffusion boundary controllable grouting material for underwater accumulation reinforcement and preparation method thereof

    CN120136479A

  • Diffusion boundary controllable grouting material for underwater accumulation reinforcement and preparation method thereof

    CN120136479B